A study on marriage and divorce law of the natives in Sarawak / Haluyah Awi - Awi, Haluyah (Faculty of Law, 1986)
Sarawak is in the north-west part of the island of Borneo. It is situated just to the north of the Equator. l The area of Sarawak is 48,250 square miles. It has a coastline of nearly 500 miles. To the north is the South China Sea. People have lived in Sarawak for a long time. Remains found in the Niah Caves indicate that men lived here over 40,000 years ago. By the Sixth Century ship started coming from distant countries to trade in Sarawak. They brought pottery beads and other manufactured goods. In return they took back product from the Sarawak forests: bird's nest, rhinoceros's horn, roatans, camphor and timber. Many of these early traders were Chinese, later they were Indians and Hindus. 2 These traders were followed by Arab and Malay merchant who brought the Muslim religion to the coastal people. Sarawak came to be ruled by the Sultan of Brunei, although for a long time the name "Sarawak" was only given to the land in the west around the Sarawak River. In 1839 there was a rebellion in this area against the Sultan of Brunei. An English- man called James Brooke visited Sarawak at this time and helped to end the rebellion. 3 In return he was made Governor and Raja of Sarawak. At this time the country stretched from Tanjong Datu to the Samaranan River. The people of the country were troubled by head-hunting and piracy. With the help of the British navy, James Brooke defeated the pirates who lived around the Lupar and Saribas rivers and extended his rule to the Land of what are now the Second Division. Later his territories were extented to the Rejang River and then as far up the coast as Bintulu. 4 When James Brooke died his nephew, Charles Brooke became Raja. More territory was gained for Sarawak when the people who lived in the Baram River area rebelled against the Sultan of Brunie. The Sultan was unable to control the rebellion and in 1882 gave the area to Sarawak, it form much of what is now the Fourth Division. In a similar way the Trisan and Limbang together with the Lawas region, which was obtained from the British North Borneo Company, they form the Fifth Division. 5